Gender identity in female soccer players - Wilinski, W. (Human Movement, 2012)
The aim of this study was to define the relationship between gender identity, the perception of the body, depressiveness, and aggression in female football players who represent different levels of competence (playing in the premier league vs. second league) and seniority in sport. Methods. Research was carried out on female football players (aged 16-31 years) playing in the premier league (N = 49) and second league (N = 45). Data were obtained with the use of: the Body Image Evaluation Questionnaire by Mandal, developed on the basis of Franzoi's concepts; Kuczyn'ska's Gender Assessment Inventory (IPP) adapted from the Bem Sex Role Inventory (BSRI), which diversifies individuals in terms of their gender identity in accordance to the Gender Schema Theory by Bem; the Beck Depression Inventory, translated by Lewicka and Czapin'ski; and the Buss-Durkee Inventory, adapted by Kosewski with comments from Stanik. To find a relationship between the mentioned variables, statistical analysis was carried out by use of ANOVA, the t test, the ?2 test and correlation coefficients. Results. The obtained research results indicate that, among female football players, the following occurs: a predominance of androgynous gender identities and a deficiency of its other types, a higher level of masculinity than among non-training women, a more favorable perception of body-as-process, a higher evaluation of body-as-object, along with an increase of masculinity and a decrease in indirect aggression at higher competition levels. Conclusions. The application of the masculinity dimension by female football players with androgynous gender identity is probably an effective strategy for survival in conditions that are unsuitable and gender-inappropriate in typical masculine sports.